(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The study aimed to understand the self-efficacy that teachers have regarding school motivation to learn, based on methodologies that develop creativity. Qualitative research was developed, which, through a case study with teachers from educational establishments in Los Ríos region, seeks to generate collaborative and interdisciplinary work spaces through creative agents (creative industry professionals). The data collection instrument applied was a script of open questions, associated with the central themes of the study; teaching self-efficacy, motivation and creativity. The results prioritize teacher self-efficacy, that is the importance of the beliefs that teachers have about their abilities, as the determining axis of their didactic action and the learning of their students. In conclusion, it is planned to prioritize the development of autonomy, communication, and life project in students through teaching expectations and strategies that enhance the idea of ​​installing educational spaces and environments oriented towards a comprehensive learning model (different from the traditional model in classroom) with a particular meaning in the educational experience.